(3efLO GdebQFjf heQTO GdWGdHjfs - (3eMeO Hf eMeO Hf eMeO Hf Ydj Hf jhSa, CHh GdNjQ, TeS GdOjf, GdYeQj GdOeTbqj Ke GdTjQGRj GdTGaYqj, GdTgjQ HGHf GdLRQj,J (B833 (3g` s
(3ChdgG (B:s
(3bGd GHh GdbGSe GdgPdi SCd eGdc QVi Gddg Yfg Yf GdHSedI abGd GdSfI GdLgQ HgG s
(3BNQgG (B:s
(3ajgG GSe Gddg eKd ShQI GdbeQ hShQI GdQMef hGbJQHJ GdSGYI hGdQMef s
(3fGbUI GdGNQ jJdhgGs
(3hQbI ai GdabIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B45 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B291s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3eJaQbGJs